2017
DOI: 10.1177/1757913917698003
|View full text |Cite
|
Sign up to set email alerts
|

Planning for sedentary behaviour interventions: office workers’ survey and focus group responses

Abstract: Multiple behavioural strategies were identified, which appear to be appropriate for sedentary behaviour change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…Task-based and phone-based types of strategies as well as strategies pertaining to work breaks and listening to your body were common across each of the intervention targets. This is in line with previous research, with strategies such as these reported to be regularly used [ 33 , 34 ] and potentially feasible to implement [ 35 , 36 ] in interventions to reduce workplace sitting time. The popularity of nominating phone-based prompts suggests this was highly appropriate for the tasks undertaken in the workers job roles.…”
Section: Discussionsupporting
confidence: 90%
“…Task-based and phone-based types of strategies as well as strategies pertaining to work breaks and listening to your body were common across each of the intervention targets. This is in line with previous research, with strategies such as these reported to be regularly used [ 33 , 34 ] and potentially feasible to implement [ 35 , 36 ] in interventions to reduce workplace sitting time. The popularity of nominating phone-based prompts suggests this was highly appropriate for the tasks undertaken in the workers job roles.…”
Section: Discussionsupporting
confidence: 90%
“…The interview responses suggested that interventions should include education about sitting guidelines, health and emotional consequences of prolonged sitting and the benefits of reducing sitting time; prompts to serve as reminders to break up sitting; environmental modification, such as the provision of height-adjustable desks to alternate between sitting and standing without disrupting work; and changes to social and organisational support. Previous studies [71][72][73] have reported similar findings that breaks from prolonged sitting need to be seen as a "normal" activity in the workplace in order to prevent perceived criticism from colleagues. Organisational support would address this change.…”
Section: Discussionmentioning
confidence: 86%
“… - Difficult concentrating when standing - Needing further instruction on how to engage with strategies - Need appropriate footwear for standing - Individual frustrations with strategies (see Strategy-specific barriers and facilitators) Habit: “ ... I have the intention, but I forget to get up ...” Employee, intervention study [ 20 ] Individual choice: “I’ve gone from a standing up for 10 hours a day job, so I enjoy the sitting” Employee, non-intervention study [ 48 ] Facilitators Facilitators - Individual motivation or commitment - Feeling personal benefits from reducing sitting - Individual motivation or personal challenge - Awareness of amount of time spent sitting - Sitting less becoming habitual - Experiencing health benefits from sitting less (such as reduced tiredness, greater concentration or alleviating musculoskeletal problems) - Perceived improvement in concentration/productivity - Having the choice and flexibility to change posture Individual motivation: “I used to make a conscious effort to get up out of my desk, talk to people, interact. It comes down to the individual.…”
Section: Resultsmentioning
confidence: 99%